Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Bus Metrotrans PT.Transjakarta Rute Pulogadung–Pondok Gede. - Satolop Kevin; Mariah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to explain the influence of the Price and service quality towards costumer satisfaction on Metrotrans Bus of PT Transjakarta Pulogadung – Pondok gede Route in partial and simultaneous. This research use quantitative approach. The amount of samples taken are 100 people using purposive sampling technique. The measurement used in the form of a questionnaire distributed through google form and data analyzed by SPSS. The analysis used is validity test, reliability test, classic assumption test, and hypothesis test. The result of the research found that: according to the partial result on price have not influence to costumer satisfaction , according to the partial result on service quality have influence to costumer satisfaction , and according to the simultaneous test result on price and service quality have together influence on costumer satisfaction.